Enterprise architecture : making one out of many build tomorrow's foundation today. - Mancuso, Wil (SOA webservices journal.)
Service oriented architectures are emerging quickly as the commercial world's answer to a flexible, standards-based infrastructure. In the world of government IT, enterprise architecture through enterprise integration is its equivalent.